Communication Skills in Psychology: Array - Munteanu (Moisă), Valentina-Beatrice (New Trends in Psychology, 2021)
We all do not want to communicate effectively at any time and in front of any person, freely, fluently, without having the feeling of difficulty in expressing clearly, correctly and concisely, our point of view on a particular topic. Communication was and is the most important step in establishing the relationship with the client. We have in our arsenal a series of elements: words, facial expressions, techniques, through which we can exchange messages. For the psychologist, complete communication is an active process of transmitting, receiving and decoding information, through which the psychologist / client communication partners, through the exchange of linguistic and non-linguistic messages, interact. In particular, it is a need for the psychologist to have listening skills. The psychotherapist-client relationship, present one of the fundamental elements aimed at psychotherapy. In psychotherapy communication acquires a therapeutic role and makes the referral of medical psychology. When we begin a therapeutic process, which involves communication, interaction, the purpose must not be clarified. Formulation of the problem, objectives, hypotheses, the problem it comes with.